Faktor – Faktor Yang Mempengaruhi Nilai Perusahaan Food and Beverage Di BEI - Tiyana, Ursulla Rut Avena; Surjadi, Lukman (Jurnal Paradigma Akuntansi, 2025)
High corporate value has an important role in the prosperity of shareholders. Investors who already have confidence in a company will be interested in buying company shares and can increase the value of the company. The purpose of this study was to determine the effect of firm value on firm size, profitability, liquidity and leverage. The technique used is the classical assumption test, descriptive statistical analysis, multiple linear regression, determinant coefficient, and hypothesis testing. The method used is purposive sampling with data obtained from 35 food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The data is processed using SPSS 25 software. The results of this study indicate that profitability, liquidity, and leverage have a positive and significant effect on firm value, but firm size has negative and significant effect on firm value.